The Application of Nanofluids for Enhanced Oil Recovery: Effects on Interfacial Tension and Coreflooding Process - Joonaki, E.; Ghanaatian, S. (Petroleum science and technology, 2014)
Most oil reservoirs around the world are experiencing their second half of life. Hence, the necessity of appropriate enhanced oil recovery (EOR) method as a more efficient technology gets further importance. Nanotechnology is an advanced technology that has proved its potential to enhance oil recovery. In this study, some selected types of nanoparticles were used, which were aluminum oxide, iron oxide, and silicon oxide treated by silane, as EOR agents during different flooding scenarios and EOR experiments under surface conditions. For the first time, the application of propanol as a dispersing agent of nanoparticles and EOR agent in the formation was investigated by this research work. In order to examine the recovery mechanisms of nanofluids, interfacial tension (IFT), and contact angle measurements between different concentrations of nanofluids and crude oil were measured. Then, several coreflood experiments were conducted to investigate their impacts directly on recoveries. The experiment results show that the nanofluids can decrease the IFT between water and oil phases and make the solid surface more neutral wet. Results indicate that aluminum oxide and silicon oxide treated by silane are good agents for enhanced oil recovery, while silicon one changes rock wettability more in addition to reduction of interfacial tension between oil and water. According to the results the future expectation is that these nanoparticles with their dispersing agent could mobilize more oil in the pore network at field scale to improve oil recovery.